Is It Live or Is It AR?. - Bolter, J.D.
By blending digital creations with our view of the world, augmented reality is set to transform the way we entertain and educate ourselves. Mobile mixed reality call forth new media forms that skillfully combine the present and the past, historical fact and its interpretation, entertainment and learning. AR and mobile technology have the potential to make the world into a stage on which we can be the actors, participating in history as drama or simply playing a game in the space before us.
Keywords: Augmented reality; Computer game; Digital creation; Entertainment; Learning; Mobile technology